Blocking miR530 Improves Rice Resistance, Yield, and Maturity - Li, Yan; Wang, Liang-Fang; Bhutto, Sadam Hussain; He, Xiao-Rong; Yang, Xue-Mei; Zhou, Xin-Hui; Lin, Xiao-Yu; Rajput, Aisha Anum; Li, Guo-Bang; Zhao, Jing-Hao; Zhou, Shi-Xin; Ji, Yun-Peng; et al. (Frontiers in Plant Science, 2021)
MicroRNAs fine-tune plant growth and resistance against multiple biotic and abiotic stress. The trade-off between biomass and resistance can penalize crop yield. Here we show that rice miR530 regulates blast disease resistance, yield, as well as growth period. While overexpression of miR530 results in compromised blast disease resistance, reduced grain yield, and late maturity, blocking miR530 using a target mimic (MIM530) leads to enhanced resistance, increased grain yield, and early maturity. Further study revealed that the accumulation of miR530 was decreased in both leaves and panicles along with the increase of age. Such expression patterns were accordant with the enhanced resistance from seedlings to adult plants, and the grain development from panicle formation to fully-filled seeds. Divergence analysis of miR530 precursor with upstream 1,000-bp promoter sequence in 11 rice species revealed that miR530 was diverse in Oryzae sativa Japonica and Oryzae sativa Indica group, which was consistent with the different accumulation of miR530 in Japonica accessions and Indica accessions. Altogether, our results indicate that miR530 coordinates rice resistance, yield, and maturity, thus providing a potential regulatory module for breeding programs aiming to improve yield and disease resistance.